Intravenous thrombolysis for acute ischaemic stroke in patients on direct oral anticoagulants. (9th March 2018) - Touzé, E.; Gruel, Y.; Gouin‐Thibault, I.; De Maistre, E.; Susen, S.; Sie, P.; Derex, L.
Abstract : Background and purpose: Whereas intravenous thrombolysis (IVT) is allowed for acute ischaemic stroke in patients on vitamin K antagonists with international normalized ratio ≤1.7, there are no similar recommendations for patients on direct oral anticoagulants (DOACs), notably due to the lack of coagulation tests to assess the therapeutic effects. Although the literature is scarce, consisting of small case series and retrospective studies, considering the frequency of this situation the French Vascular Neurology Society and the French Study Group on Haemostasis and Thrombosis have worked on a joint position paper to provide a practical position regarding the emergency management of ischaemic stroke in patients on DOACs. Method: Based on a review of the literature, the authors wrote a first text that was submitted to a broad panel of members from the two societies. The text was then amended by the authors to address experts' comments and to reach a consensus. Results: In patients with normal renal function and who stopped the DOAC for at least 48 h, the management should not differ from that in patients without oral anticoagulant. In patients who are still on DOACs, mechanical thrombectomy is encouraged preferentially when applicable in first line. Otherwise, when specific tests are available, values <50 ng/ml indicate that IVT is allowed. In the absence of specific tests, standard tests (thrombin time, prothrombin time and activated partial thromboplastin time) can be used for dabigatran and rivaroxaban, although interpretation of these tests may be less reliable. In some patients on dabigatran, idarucizumab may be used before IVT. Conclusions: In this expert opinion paper, it is suggested that IVT can be performed in patients selected according to the time elapsed since the drug was last taken, renal function, type of hospital where the patient is admitted and plasma concentration of DOAC.